What are the prospects for Mozambique to diversify its economy on the back of 'local content'? - Dietsche, Evelyn; Esteves, Ana Maria (WIDER Working Paper Series, 2018)
In recent years, Mozambique has made international headlines for the significant hydrocarbon deposits found offshore. These have increased the country's extractive resource endowments, in addition to its mining and onshore natural gas sector. It is expected that these industries will contribute to economic diversification and social development, not least by means of procuring locally produced goods and services and hiring Mozambicans. A key factor to achieve this is building domestic capital?in people, institutions, and infrastructure.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; extractive industries / indústrias extractivas; natural resources / recursos naturais; private sector - CSR (corporate social responsibility) / setor privado - RSC (responsabilidade social corporativa); ⛔ No DOI found

Mozambique plantation leaves no land or jobs for villagers - Adler, Nils (New Internationalist, 2018)
In northern Mozambique, villagers were promised jobs to replace land taken for forestry. Five years later, they’re still waiting, discovers Nils Adler.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GD - Lichinga; GP - Niassa; L - english / inglês; agriculture / agricultura; governance / governação; land governance / gestão de terra; private sector / setor privado

The Project for Supporting the Promotion of Nacala Corridor Development - Final Report - Japan International Cooperation Agency (JICA) (Japan International Cooperation Agency (JICA), 2018)
Final JICA report on Nacala Corridor Development Project, whose objectives include: to clarify organizations for promoting and coordinating the implementation of development strategies for the Nacala Corridor Region in accordance with PEDEC-Nacala and to prepare for the implementation of high priority projects in accordance with PEDEC-Nacala. The study project commenced in April 2012 and the final study report was produced in April 2015.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - Nacala; G - central / centro; G - north / norte; GD - Lichinga; GP - Cabo Delgado; GP - Nampula; GP - Niassa; GP - Tete; GP - Zambézia; L - english / inglês; development partners / parceiros de cooperação; extractive industries / indústrias extractivas; infrastructure / infrastrutura; natural resources / recursos naturais; private sector / setor privado

Extractives and economic diversification in Mozambique: will local content do the trick? (2018)
Research Findings - It is unlikely that the extractives sector can any time soon be used to finance visionary transformation strategies aimed at achieving economic diversification. Due to the country’s fiscal situation and delays in developing the offshore natural gas sector, it seems that extractives will not provide additional revenues for at least another decade, if not longer. If the fiscal crisis results in the further deterioration of the provision of public goods and services, the business environment will become worse for the country’s micro, small and medium-sized enterprises. There is the risk that the gap will widen even further between the skills and entrepreneurial capabilities available in the country, and those required by foreign investment projects and their supply chains. Such a prospect does not match well with the expectations that local content policies can provide the silver bullet for diversifying the economy.
Keywords: FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - english / inglês; extractive industries / indústrias extractivas; natural resources / recursos naturais; private sector / setor privado

Country Results Brief 2018 - Mozambique - African Development Bank (African Development Bank, 2018)
Over the last decade, Mozambique has been one of the fastest-growing African economies, enjoying average economic growth of about 8% between 2004 and 2015. It received strong support from the international community during the period (for example, in 2014 it received US$2 billion in official development assistance). In parallel, the country has embarked on major reforms — especially fiscal reforms and tax administration — and has opened up to foreign investment, particularly for the exploitation of its natural resources.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; agriculture / agricultura; development partners / parceiros de cooperação; governance / governação; infrastructure - energy / infrastrutura - energia; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura; private sector / setor privado

Mozambique’s private sector in the context of conflict - Macuane, José Jaime (International Growth Centre, 2018)
This case study analyses the interactions between conflict and private sector development in Mozambique. In the 42 years following its independence, Mozambique faced a 16-year civil war from 1976/77 to 1992, an interim period of peace that lasted 20 years, and recurring, low-level conflict involving the same belligerents since 2013. This case study examines the conflict dynamics in post-independence Mozambique, and how the private sector has developed in response to both conflict and peace.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; conflict / conflito; private sector / setor privado

O agronegócio no desenvolvimento do meio rural em Moçambique: perceção e análise das cadeias de valor de milho e da mandioca na província de Nampula - Linha, Paulo (Universidade de Lisboa, 2017)
O Agronegócio em Moçambique poderá ser um factor dinamizador da agricultura, chave para o desevolvimento económico, elemento para a equidade no desenvolvimento social e fundamental para a redução da pobreza e da fome. O estudo analisa as perceções dos atores do agronegócio do milho e da mandioca sobre o impacto destas culturas na vida económica e social no meio rural. Diante desta perspetiva, esta pesquisa teve como objetivo investigar prospectivamente as cadeias de valor das culturas do milho e da mandioca, no corredor de Nacala, com vista a identificar formas de potenciar o desenvolvimento do agronegócio como fator dinamizador da promoção do desenvolvimento socioeconómico sustentável no meio rural. Os resultados alcançados indicam que em Moçambique, de forma geral, o agronegócio do milho e da mandioca é potencial pilar dinamizador que poderá contribuir para o desenvolvimento da agricultura e impulsionar o crescimento económico e o desenvolvimento social se o Estado colocar-se na dianteira na criação, nas zonas de produção, de infraestruturas públicas para a prática de uma agricultura economicamente sustentável e uma legislação flexível e promotora de um clima propício para o agronegócio. Com as infraestruturas públicas criadas nos centros de produção deve-se optar, pelo envolvimento de todos atores do agronegócio num sistema de Integração e Coordenação Vertical, apostando na transformação da baixa renda da agricultura rural em agricultura comercial e competitiva para que efetivamente o agronegócio seja um dos pilares para o combate da fome e da pobreza no meio rural. A Integração e Coordenação Vertical, significa a existência de instituições âncoras que se dedicam a puxar a atividade do agronegócio dos produtores locais na base contratual. Esta forma promete rápida integração ao mercado, crescimento económico, inovação tecnológica, ao mesmo tempo em que protege os direitos e a autonomia do produtor sob regime de integração e coordenação. Agribusiness in Mozambique could be a driving force for agriculture, key to economic development, an element for equity in social development and fundamental to reducing poverty and hunger. The study analyzes the perceptions of corn and cassava agribusiness actors on the impact of these crops on economic and social life in rural areas. The objective of this research was to investigate prospectively the corn and cassava value chains in the Nacala corridor in order to identify ways to promote the development of agribusiness as a driving force for the promotion of sustainable socioeconomic development in the environment rural. The results indicate that, in general, corn and cassava agribusiness in Mozambique are potential pivotal factors that could contribute to the development of agriculture and boost economic growth and social development, if the government takes the initiative to build public infrastructures for an economic sustainable agriculture as well as create a flexible legislation that promotes a proper environment for agribusiness. With the public infrastructures created in the production centers, one must opt for the involvement of all agribusiness actors in a system of Integration and Vertical Coordination, betting on the transformation of low income from rural agriculture into commercial and competitive agriculture so that agribusiness is effectively a pillar to combat hunger and poverty in rural areas. Integration and Vertical Coordination means the existence of anchor institution dedicated to pull the agribusiness activity of the local producers in the contractual basis. This form promises rapid market integration, economic growth, technological innovation, while protecting the rights and autonomy of the producer under integration and coordination.
Accepted: 2018-04-09T13:15:08Z
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; agriculture / agricultura; private sector / setor privado

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Final Report 2011-2015 - Tvedten, Inge; Tuominen, Minna; Rosário, Carmeliza (ORGUT Consulting AB, 2016)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; institutions / instituições; poverty / pobreza; private sector / setor privado

Socio-economic impacts of private land use investment on rural communities: Industrial forest plantations in Niassa, Mozambique - Bleyer, Maja; Kniivilä, Matleena; Horne, Paula; Sitoe, Almeida; Falcão, Mário Paulo (Land Use Policy, 2016)
East Africa has experienced an increase of private land use investments in the past years. Rural households have consequently faced crucial changes in their livelihoods. This paper explores the socio-economic impacts of industrial forest plantations on rural communities in Niassa, Mozambique. According to our results private forest plantations have the potential to positively impact local people’s wealth and well-being, if enough emphasis is given to minimizing the negative impacts. The household survey data of 218 observations from five villages were analyzed using binary and multinomial logistic regression analyses. The study shows that forest plantations have threatened the basis of traditional rural livelihoods by reducing the availability of natural resources and through the relocation of agricultural plots. However, investments have also supported the diversification of livelihood strategies in the communities by providing formal employment and by increasing business and trading activities. As growing population and traditional agricultural practices have led to the overexploitation of natural resources, non-natural resource-based livelihood strategies increase the resilience of a household. The majority of respondents reported plantations to have either no overall impact or a positive impact on the well-being of their household. According to our results, socio-economic household characteristics only marginally explain respondents’ perceptions of the impacts of forest plantations but perceptions differ significantly between individual villages.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; agriculture / agricultura; governance / governação; land governance / gestão de terra; private sector / setor privado

Corporate Social Responsibility in Mozambique - Kaufmann, Friedrich; Simons-Kaufmann, Claudia (Corporate Social Responsibility in Sub-Saharan Africa: Sustainable Development in its Embryonic Form, 2016)
Mozambique is a young African country with a strong growing economy and increasing foreign direct investment. We can observe a rising number of Corporate Social Responsibility (CSR) projects and activities in the country. Nevertheless there is still no systematic approach or coordination through public authorities or the business sector itself. CSR is mainly motivated by immediate own company needs like training or health of workers. We also find philanthropy projects as well as projects supporting local communities on development priorities, mainly health, education and community development. CSR, as part of a business concept, is mainly limited to large companies and foreign investors with international experience and less to small and medium-sized enterprises (SMEs). Many national companies, especially SMEs still do not have the CSR capacity or the respective mind set. First of all it is the mega projects that have their professional CSR departments and budgets. In the mining sector a CSR component is now compulsory by law since 2014.As public institutions are weak, CSR in Mozambique is more about “CSR towards compliance” and sometimes less about “CSR beyond compliance”. Strong views are expressed by civil society that for example the enforcement of labour legislation within companies is weak and hardly controllable by the government. This fact combined with corruption issues makes CSR towards compliance of existing labour, environmental, fiscal laws and other regulation an important topic. Nevertheless it is questionable if this should be considered as CSR. CSR in general is sometimes seen as “green washing” by big investors, benefitting on the other hand from generous tax exemptions and special deals with the government. Nevertheless, CSR is of growing importance in Mozambique and as the new mining CSR law shows, government is slowly entering the CSR landscape. A better coordination and public-private dialogue about CSR is necessary in order to make it a more useful and an efficient instrument for development. Nevertheless it should be clear that CSR is voluntary and in a globalized economy with international value chains becomes more and more an international issue.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; civil society / sociedade civil; private sector - CSR (corporate social responsibility) / setor privado - RSC (responsabilidade social corporativa); private sector / setor privado

Indústria extractiva e desenvolvimento local: O papel da responsabilidade social empresarial - Langa, Epifânia; Massingue, Nelsa (Desafios para Moçambique, 2014)
A entrada de grandes investimentos de capitais estrangeiros na área de recursos minerais e energia, nos últimos anos, tem levantado várias questões sobre o papel dos mega ‑projectos no desenvolvimento económico e social em Moçambique, gerando um debate sem consenso. Uma das temáticas do debate é a responsabilidade social empresarial (RSE). Acções de RSE como a construção de infra ‑estruturas sociais para a educação e a saúde, a geração de emprego, entre outras são muitas vezes referenciadas em muitos discursos, principalmente políticos e de empresas, como aspectos positivos que complementam as acções do governo, devendo por isso ser promovidas e valorizadas.1 Entretanto, estes discursos muitas vezes negligenciam componentes não menos importantes como a intenção das empresas ao desen‑ volver iniciativas sociais, o risco das comunidades se tornarem dependentes destes mega ‑projectos e a possibilidade de fragilização do papel do Estado (Schroeder & Schroeder, 2004).
Keywords: G - Mozambique / Moçambique; L - portuguese / português; extractive industries / indústrias extractivas; natural resources / recursos naturais; private sector - CSR (corporate social responsibility) / setor privado - RSC (responsabilidade social corporativa); private sector / setor privado